The right way to write how to write effective business letters, reports, memos and e-mail - Morris, Rupert
The Right Way to Write is a practical and inspiring guide to better business writing. Using simple exercises and dozens of samples letters, Rupert Morris shows you how to cut through the hazards of corporate waffle, avoid the pitfalls of English grammar and write positively and effectively. Whether you dictate your letters or write everything yourself, whether you want to send a short e-mail message or produce a 16-page report, you will learn how to organize your thoughts, break free of bad habits and write clearly and with purpose.